To Measure or Not to Measure: Direct Oral Anticoagulant Laboratory Assay Monitoring in Clinical Practice - Tania Ahuja; Veronica Raco; Sharonlin Bhardwaj; David Green (Advances in Hematology)
The need for therapeutic drug monitoring of direct oral anticoagulants (DOACs) remains an area of clinical equipoise. Although routine monitoring may be unnecessary given predictable pharmacokinetics in most patients, there may be altered pharmacokinetics in those with end organ dysfunction, such as those with renal impairment, or with concomitant interacting medications, at extremes of body weight or age, or in those with thromboembolic events in atypical locations. We aimed to assess real-world practices in situations in which DOAC drug-level monitoring was used at a large academic medical center. A retrospective review of the records of patients who had a DOAC drug-specific activity level checked from 2016 to 2019 was included. A total of 119 patients had 144 DOAC measurements (apixaban (n = 62) and rivaroxaban (n = 57)). Drug-specific calibrated DOAC levels were within an expected therapeutic range for 110 levels(76%), with 21 levels (15%) above the expected range and 13 levels (9%) below the expected range. The DOAC levels were checked in the setting of an urgent or emergent procedure in 28 patients (24%), followed by renal failure in 17 patients (14%), a bleeding event in 11 patients (9%), concern for recurrent thromboembolism in 10 patients (8%), thrombophilia in 9 patients (8%), a history of recurrent thromboembolism in 6 patients (5%), extremes of body weight in 7 patients (5%), and unknown reasons in 7 patients (5%). Clinical decision making was infrequently affected by the DOAC monitoring. Therapeutic drug monitoring with DOACs may help predict bleeding events in elderly patients, those with impaired renal function, and in the event of an emergent or urgent procedure. Future studies are needed to target the select patient-specific scenarios where monitoring DOAC levels may impact clinical outcomes.